Modeling and Simulations of Mosquito Dispersal. The Case of Aedes albopictus - Claire Dufourd (Biomath, 2012)
To prevent epidemics of mosquito-transmitted diseases like Chikungunya in R´eunion Island, we develop tools to control its principal vector, Aedes albopictus. Biological control tools, like the Sterile Insect Technique (SIT), are of great interest as an alternative to chemical control tools which are very detrimental to environment. The success of SIT is based on a good knowlege of the biology of the insect, but also on an accurate modeling of the insects distribution. We model the mosquito dispersal with a system of coupled parabolic PDEs. Considering vector control scenarii, we show that the environment can have a strong influence on mosquito distribution and in the efficiency of vector control tools.